Method for enhancing electricity generation of microbial fuel cell by interface modification of free magnetic-rich carbon three-dimensional biological anode and bacteria
The hydrophilic magnetic nano-Fe3O4@ molded porous carbon composite material is prepared as a three-dimensional bioanode by solvent thermal method, which solves the problem of low extracellular electron transfer efficiency of microbial fuel cells and improves the overall performance and electricity production performance of MFC.
Patent Information
- Application Number
- CN202410699390.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-31
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-05-31
AI Technical Summary
The low extracellular electron transfer efficiency of microbial fuel cells (MFCs) limits its practical application. The poor crystallinity and hydrophobic properties of traditional Fe3O4 nanoparticles are not conducive to microbial adhesion and extracellular electron transfer of electroactive bacteria.
The hydrophilic magnetic nano-Fe3O4@ molded porous carbon composite material is prepared by solvothermal method as a three-dimensional bioanode. The solvent-thermal reaction of trisodium citrate and sodium acetate at high temperatures is carried out to generate highly hydrophilic magnetite particles, combined with The structure of porous carbon improves the hydrophobic properties of the carbon balls, provides more electron transfer sites, and promotes extracellular electron transfer of microorganisms.
It improves the overall performance of microbial fuel cells, enhances the electron transfer efficiency between bacteria and archaea, improves the conversion rate and output voltage of the bioanode, promotes the colonization and growth of microorganisms, and significantly improves the power generation performance of MFC.
Smart Images

Figure HDA0004870639340000011 
Figure HDA0004870639340000012 
Figure HDA0004870639340000013
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microbial fuel cells, and in particular to a method for enhancing electricity generation in a microbial fuel cell by modifying the interface of a free magnetic carbon-rich three-dimensional bioanode and bacteria. Background Art
[0002] Microbial fuel cells (MFCs) are a typical bioelectrochemical system that uses the energy metabolism of electroactive bacteria to collect electricity from organic substrates. They have attracted widespread attention due to their great potential for both sustainable clean energy production and organic wastewater, waste gas, and solid waste treatment. Although great progress has been made in recent years, the limited extracellular electron transfer efficiency of microorganisms has restricted the practical application of MFCs.
[0003] It is feasible to regulate the extracellular electron transfer of microorganisms through electron transfer mediators. It can shorten the complex electron transfer process in the anaerobic process, improve the degradation rate of digested substrates and the output of electrons, strengthen the connection between bacteria, increase the conductivity of the anaerobic system, and thus enhance the extracellular electron transfer process of microorganisms. Nano-Fe3O4 has good quantum size effect, strong electromagnetic properties, large specific surface area, small size distribution, low toxicity, high biocompatibility, and strong adsorption capacity. It can be used as an ideal medium for electron transfer in anaerobic processes. However, the Fe3O4 nanoparticles obtained by the traditional coprecipitation method have poor crystallinity, which reduces the conductivity and magnetization intensity, and is prone to agglomeration. The thermal decomposition of organic metals and coordination compounds in non-polar solutions has been successfully used to synthesize monodisperse magnetic nanocrystals with high crystallinity and small size at the nanoscale. However, the magnetic nanocrystals synthesized by these methods are usually hydrophobic and have low magnetization intensity.
[0004] Biochar is also often used in anaerobic digestion due to its non-biotoxicity, high specific surface area, numerous pores that can be modified, and low price. It can promote direct electron transfer. The high specific surface area and porous structure of biochar can significantly improve the mass transfer efficiency, especially the shaped porous biochar material, which can provide a three-dimensional spatial network structure to facilitate the adhesion and growth of microorganisms. In addition, loading Fe3O4 nanoparticles onto shaped porous biochar can effectively solve the problems of agglomeration and loss of nano Fe3O4 particles. However, biochar is generally calcined under high temperature and anoxic conditions, and is usually hydrophobic in nature. The higher the calcination temperature, the stronger the hydrophobicity. Loading hydrophobic magnetic Fe3O4 nanocrystals onto biochar with the same hydrophobic properties is not conducive to the attachment of microorganisms, hindering the development of biofilms and the extracellular electron transfer of electroactive bacteria. Summary of the invention
[0005] In view of this, the present invention proposes a method for enhancing the electricity production of microbial fuel cells by free magnetic carbon-rich three-dimensional bioanode and bacterial interface modification to solve the above problems.
[0006] The technical solution of the present invention is achieved in this way:
[0007] A method for enhancing electricity generation of a microbial fuel cell by interfacial modification of a free magnetic carbon-rich three-dimensional bioanode and bacteria, wherein the preparation method of the free magnetic carbon-rich three-dimensional bioanode comprises the following steps:
[0008] (1) crushing biomass to obtain biomass powder, mixing the biomass powder with phenol and a catalyst to carry out a liquefaction reaction to obtain a biomass liquefied product;
[0009] (2) reacting the biomass liquefaction product with formaldehyde to obtain a resin reaction product, and subjecting the resin reaction product to a hydrothermal reaction to obtain a hydrothermal reaction product;
[0010] (3) mixing the hydrothermal reaction product and zinc chloride and placing the mixture in a mold, demolding, carbonizing, pickling, and washing with water to obtain a formed porous carbon;
[0011] (4) An iron source, trisodium citrate and ethylene glycol are mixed, added into the formed porous carbon and stirred, and then sodium acetate is added and mixed to obtain a mixed material, and the mixed material is subjected to a solvothermal reaction to obtain a free magnetic carbon-rich three-dimensional bioanode.
[0012] Furthermore, in step (1), the mass ratio of biomass powder to phenol is 1:1-6; the catalyst is one or more of sulfuric acid, phosphoric acid, and p-toluenesulfonic acid, and the mass ratio of the catalyst to biomass powder is 0.1-0.6:1.
[0013] Furthermore, in step (1), the temperature of the liquefaction reaction is 120-170° C., and the reaction time is 0.5-5 h.
[0014] Furthermore, in step (2), the mass ratio of formaldehyde to biomass liquefaction product is 0.8-3:1, the temperature of the resinification reaction is 50-100°C, the resinification reaction time is 30-120min, the temperature of the hydrothermal reaction is 100-160°C, and the hydrothermal reaction time is 6-24h.
[0015] Furthermore, in step (3), the mass ratio of biomass powder to zinc chloride is 1:1.6-4.8, the shape of the mold is one of spherical, cylindrical, and cubic, the carbonization is carried out at 400-1000°C for 30-180min under a nitrogen atmosphere, the pickling is carried out using one of hydrochloric acid and sulfuric acid, and the concentration of the pickling is 0.1-2 mol / L.
[0016] Furthermore, in step (4), the iron source is one or both of ferric chloride and ferric nitrate, the iron source concentration is 0.05-0.35 mol / L, the trisodium citrate concentration is 8-80 mmol / L, the formed porous carbon concentration is 20-120 g / L, the sodium acetate concentration is 0.2-1.5 mol / L, the solvent thermal reaction temperature is 200-220°C, and the reaction time is 4-15 h.
[0017] Furthermore, the bacterium is the electroactive bacterium Shewanella onesidensis MR-1.
[0018] Further, the OD in the Shewanella anolyte is 600 0.9-1.1.
[0019] Furthermore, the MFC reactor was constructed and started: a double-chamber reactor was used, the anode chamber and the cathode chamber were separated by a Nafion 117 proton exchange membrane, the anode material was a carbon brush, and the cathode material was a graphite rod.
[0020] Furthermore, the free magnetic carbon-rich three-dimensional bioanode was added to the anode chamber, and the electroactive bacteria Shewanella onesidensis MR-1 was selected as the inoculum. The MR-1 suspension was dispersed in the anode liquid and inoculated into the MFC reactor. Nitrogen was bubbled for 15 minutes to form an anaerobic environment. The composition of the anode liquid: 50mmol / L phosphate buffer (formula: 10.36g / L Na2HPO4·12H2O, 3.32g / LNaH2PO4·2H2O, 0.31g / L NH4Cl and 0.13g / L KCl), 1mL / L trace element liquid, carbon source and electron donor were added. The cathode liquid was a mixture of potassium ferrocyanide (50mmol / L) and potassium chloride (50mmol / L). The cathode and anode were connected through a 1kΩ external resistor, and a Keithley multimeter was used to collect output voltage data, with one point collected every 10 minutes. The ambient temperature of the MFC reactor was 30℃.
[0021] Furthermore, a free magnetic carbon-rich three-dimensional bioanode and bacterial interface modification are used in the degradation of paraxylene.
[0022] Furthermore, the MFC reactor anode liquid also contains OD 600 It is 0.9-1.1 for Klebsiella HN02.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention adopts a solvothermal method to prepare a hydrophilic magnetic nano-Fe3O4@ shaped porous carbon composite material with strong electromagnetic properties, large specific surface area and high biocompatibility. The composite material can be used as a three-dimensional bioanode in MFC, which is beneficial to the attachment of microorganisms and maximizes their colonization space. At the same time, as an excellent electron mediator, it can promote the extracellular electron transfer efficiency of bacteria and enhance the interspecies electron transfer between bacteria and archaea, thereby improving the bioanode conversion rate and electron output, thereby improving the overall performance of MFC and promoting the practical application of MFC.
[0025] (2) The present invention uses sodium acetate as an alkali source, trisodium citrate with good biocompatibility as an electrostatic stabilizer, and ethylene glycol as a solvent and a reducing agent, and performs a solvothermal reaction at a high temperature to synthesize highly hydrophilic magnetite particles. The three carboxyl groups in trisodium citrate are very hydrophilic to Fe 3+ It has a strong coordination affinity. During the solvothermal reaction, the citric acid group can be anchored on the surface of magnetite nanocrystals, enhance the dispersibility of magnetite particles, and inhibit the growth of grains, thereby obtaining small-sized, uniform-sized, highly hydrophilic magnetic Fe3O4 nanoparticles. Therefore, during the reaction, the shaped porous carbon material is put into the above-mentioned mixed solution, and the magnetic nanoparticles will grow inside and on the surface of the porous carbon-rich pore structure, improve the partial hydrophobicity of the carbon balls, and provide more electron transfer sites, improve the overall conductivity of the porous carbon, thereby accelerating the extracellular electron transfer and interspecies electron transfer process of microorganisms. In addition, the magnetic nano-Fe3O4@shaped porous carbon can be used as a three-dimensional bioanode to provide a larger surface area for microbial growth per volume of the reactor and improve the bioanode conversion rate. Secondly, the charge can be stored in the pores of the shaped porous carbon in the form of a double electric layer, which can significantly improve the performance of the three-dimensional bioanode and enhance the diversity, stability and bioelectric activity of the bacterial community.
[0026] The MR-1+HN02+Fe3O4@formed porous carbon ball system constructed in the present invention can improve the removal effect of xylene. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Example 1 Schematic diagram of power generation by efficient MFC
[0028] Figure 2 Comparison of MFC output voltage of MR-1 system, MR-1+formed porous carbon ball system, and MR-1+Fe3O4@formed porous carbon ball system
[0029] Figure 3 Fe3O4@ formed porous carbon balls
[0030] Figure 4 Comparison chart of power generation in comparative example 2
[0031] Figure 5Comparison of power generation performance of Example 2 and Comparative Example 3
[0032] Figure 6 Comparison of the degradation effects of p-xylene between Example 2 and Comparative Example 3 DETAILED DESCRIPTION
[0033] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0034] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0035] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0036] The electroactive bacteria Shewanella onesidensis MR-1 used in the embodiment of the present invention can be purchased from the Microbial Culture Collection Center.
[0037] Example 1
[0038] (1) Preparation of shaped porous carbon balls: 5g of eucalyptus powder, 15g of phenol and 0.49mL of sulfuric acid were placed in a three-necked flask in sequence and liquefied at 150°C for 2h. After the liquefied product was cooled to room temperature, it was washed with methanol, and a methanol-liquefied product was obtained after vacuum filtration, and then the methanol was removed by reduced pressure distillation to obtain a liquefied product. The liquefied product was mixed evenly with 0.72g of NaOH and 30mL of deionized water, and 17mL of 37% formaldehyde solution was added dropwise at 70°C, stirred for 30min, and then 30mL of anhydrous ethanol and 10mL of deionized water were added, and stirring was continued for 2h. Finally, 140mL of deionized water was added to dilute, and the mixture was transferred into a stainless steel reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 130°C for 24h. The hydrothermal product was obtained after washing with anhydrous ethanol and deionized water and centrifuging. The hydrothermal product was mixed with 12g ZnCl2 and filled into a spherical mold. After drying, it was placed in a tube furnace and heated to 600°C at a heating rate of 5°C / min for 90 minutes. The obtained carbon balls were washed with 1mol / L HCl solution and then washed with deionized water until neutral. After drying, the formed porous carbon balls were obtained.
[0039] (2) Preparation of magnetic carbon spheres: 2.16 g FeCl3·6H2O and 0.4 g trisodium citrate were dissolved in 40 mL ethylene glycol, added to the shaped porous carbon spheres and stirred for 30 min, then 2.4 g sodium acetate was added and stirred for another 30 min, then the mixture was transferred to a polytetrafluoroethylene-lined reactor and reacted at 200 °C for 12 h. After the reaction, the mixture was washed with anhydrous ethanol and water in turn, and dried to obtain Fe3O4@ shaped porous carbon spheres.
[0040] (3) Construction and start-up of the MFC reactor: A double-chamber plexiglass reactor was used. The effective volume of the anode chamber and the cathode chamber was 100 mL each, separated by a Nafion 117 proton exchange membrane. The anode material was a carbon brush (3 cm in diameter and 3 cm in length), and the cathode material was a graphite rod (6 mm in diameter and 10 cm in length).
[0041] (4) Fe3O4@formed porous carbon balls (20 g / L) were added to the anode chamber, and the electroactive bacteria Shewanella onesidensis MR-1 was selected as the inoculum. The MR-1 suspension was dispersed in 90 mL of the anode solution until the OD 600 The pH value was 1.0, and then inoculated into the MFC reactor, and nitrogen was bubbled for 15 minutes to form an oxygen-free environment. The composition of the anode liquid: 50mmol / L phosphate buffer (formula: 10.36g / LNa2HPO4·12H2O, 3.32g / L NaH2PO4·2H2O, 0.31g / L NH4Cl and 0.13g / L KCl), 1mL / L trace element liquid, 18mmol / L sodium lactate as a carbon source and electron donor. The cathode liquid was a mixture of 90mL potassium ferrocyanide (50mmol / L) and potassium chloride (50mmol / L). The cathode and anode were connected through a 1kΩ external resistor, and a Keithley multimeter was used to collect output voltage data, with one point collected every 10 minutes. The ambient temperature of the MFC reactor was 30℃.
[0042] Comparative Example 1:
[0043] On the basis of Example 1, two different MFC reactors, namely, the MR-1 system and the MR-1+formed porous carbon ball system, were constructed.
[0044] MR-1 system: The electroactive bacteria Shewanella onesidensis MR-1 was selected as the inoculum, and the MR-1 suspension was dispersed in 90 mL of the anolyte until the OD 600The pH value was 1.0, and then inoculated into the MFC reactor, and nitrogen was bubbled for 15 minutes to form an oxygen-free environment. The composition of the anode liquid: 50mmol / L phosphate buffer (formula: 10.36g / L Na2HPO4·12H2O, 3.32g / L NaH2PO4·2H2O, 0.31g / L NH4Cl and 0.13g / L KCl), 1mL / L trace element liquid, 18mmol / L sodium lactate as a carbon source and electron donor. The cathode liquid was a mixture of 90mL potassium ferrocyanide (50mmol / L) and potassium chloride (50mmol / L). The cathode and anode were connected through a 1kΩ external resistor, and a Keithley multimeter was used to collect output voltage data, with one point collected every 10 minutes. The ambient temperature of the MFC reactor was 30℃.
[0045] MR-1+formed porous carbon ball system: (1) Preparation of formed porous carbon balls: 5g eucalyptus powder, 15g phenol and 0.49mL sulfuric acid were placed in a three-necked flask in turn and liquefied at 150°C for 2h. After the liquefied product was cooled to room temperature, it was washed with methanol, and a methanol-liquefied product was obtained after vacuum filtration, and then the methanol was removed by reduced pressure distillation to obtain a liquefied product. The liquefied product was mixed evenly with 0.72g NaOH and 30mL deionized water, and 17mL 37% formaldehyde solution was added dropwise at 70°C, stirred for 30min, and then 30mL anhydrous ethanol and 10mL deionized water were added, and stirring was continued for 2h. Finally, 140mL deionized water was added to dilute, and the mixture was transferred into a stainless steel reactor lined with polytetrafluoroethylene, and hydrothermally reacted at 130°C for 24h. The hydrothermal product was obtained after washing with anhydrous ethanol and deionized water and centrifuging. The hydrothermal product was mixed with 12g ZnCl2 and filled into a spherical mold. After drying, it was placed in a tube furnace and heated to 600°C at a heating rate of 5°C / min for 90 minutes. The obtained carbon balls were washed with 1mol / L HCl solution and then washed with deionized water until neutral. After drying, the formed porous carbon balls were obtained.
[0046] The shaped porous carbon balls (20 g / L) were added to the anode chamber, and the electroactive bacteria Shewanella onesidensis MR-1 was selected as the inoculum. The MR-1 suspension was dispersed in 90 mL of the anode solution until the OD 600The pH value was 1.0, and then inoculated into the MFC reactor, and nitrogen was bubbled for 15 minutes to form an oxygen-free environment. The composition of the anode liquid: 50mmol / L phosphate buffer (formula: 10.36g / L Na2HPO4·12H2O, 3.32g / L NaH2PO4·2H2O, 0.31g / L NH4Cl and 0.13g / L KCl), 1mL / L trace element liquid, 18mmol / L sodium lactate as a carbon source and electron donor. The cathode liquid was a mixture of 90mL potassium ferrocyanide (50mmol / L) and potassium chloride (50mmol / L). The cathode and anode were connected through a 1kΩ external resistor, and a Keithley multimeter was used to collect output voltage data, with one point collected every 10 minutes. The ambient temperature of the MFC reactor was 30℃.
[0047] Test Example 1
[0048] The power generation performance of Example 1 and Comparative Example 1 was tested.
[0049] See also Figure 1 The Fe3O4@formed porous carbon balls of Example 1 are used as three-dimensional bioanode and magnetic electron mediator, which optimizes the colonization space of bacteria. Their porous structure has a good adsorption effect on organic substrates, can improve the bioanode conversion rate, store charges, and enhance the extracellular electron transfer and interspecies electron transfer of bacteria, thereby improving the power generation performance of MFC.
[0050] See also Figure 2 , the power generation of MFC reactors of three different systems, namely, the pure MR-1 system, the MR-1+formed porous carbon ball system, and the MR-1+Fe3O4@formed porous carbon ball system, was compared. The maximum output voltage of the pure MR-1 system was 354mV. After adding porous carbon balls (MR-1+porous carbon ball system), the maximum output voltage rose to 400mV, indicating that the porous carbon balls accelerated the extracellular electron transfer of electroactive bacteria as electron mediators. When the porous carbon balls were magnetized and added to the system (MR-1+Fe3O4@porous carbon ball system), the maximum output voltage increased to 452mV, which was attributed to the synergistic effect of the magnetic electron mediator and the porous carbon balls. As a three-dimensional bioanode, the porous structure of Fe3O4@formed porous carbon balls not only facilitates the adhesion, growth and reproduction of microorganisms, but also enriches organic substrates and improves the bioanode conversion rate. Secondly, as a magnetic electron mediator, it can closely bind to the outer surface of bacteria and accelerate the extracellular electron transfer of bacteria.
[0051] Comparative Example 2
[0052] On the basis of Example 1, the particle size of Fe3O4@ formed porous carbon balls was adjusted to 2 mm and 8 mm respectively.
[0053] Test Example 2
[0054] The particle size of the Fe3O4@ formed porous carbon balls prepared in Comparative Example 2 was detected by referring to the output voltage detection method in Example 1.
[0055] See also Figure 3 The particle size of the Fe3O4@ formed porous carbon balls prepared in Example 1 is about 5 mm.
[0056] See also Figure 4 , the effects of Fe3O4@ formed porous carbon balls with different particle sizes on MFC power generation were compared. The maximum output voltage of Fe3O4@ formed porous carbon balls with a particle size of 2 mm was 381 mV, and the maximum output voltage of Fe3O4@ formed porous carbon balls with a particle size of 8 mm was 399 mV, both of which were lower than the maximum output voltage (452 mV) of Fe3O4@ formed porous carbon balls with a particle size of 5 mm, indicating that Fe3O4@ formed porous carbon balls with a particle size that is too large or too small are not conducive to MFC power generation.
[0057] Example 2
[0058] The Fe3O4@ shaped porous carbon balls synthesized in Example 1 were used to mediate the synergistic degradation of p-xylene by Shewanella onesidensis MR-1 and Klebsiella HN02 and MFC electricity production.
[0059] Klebsiella HN02 is deposited in Guangdong Provincial Microbiological Culture Collection Center, named Klebsiella sp. HN02, the deposit number is GDMCC No: 62011, and the deposit date is November 4, 2021.
[0060] (1) Construction and start-up of the MFC reactor: A double-chamber glass reactor was used. The effective volume of the anode chamber and the cathode chamber was 350 mL each, separated by a Nafion 117 proton exchange membrane. The anode material was a carbon brush (3 cm in diameter and 5 cm in length), and the cathode material was a graphite rod (6 mm in diameter and 15 cm in length).
[0061] Using the Fe3O4@formed porous carbon balls synthesized in Example 1, 5 g / L of Fe3O4@formed porous carbon balls were added to the anode chamber. The enriched Klebsiella HNO2 was washed and centrifuged, and dispersed in 250 mL of anode solution until OD 600The pH value was 1.0, and the same amount of Shewanella onesidensis MR-1 was added, and then inoculated into the MFC reactor, and nitrogen was bubbled for 15 minutes to form an anaerobic environment. On the 0th day and the 2nd day, 10μL of p-xylene liquid was added as the only carbon source and electron donor. The magnetic stirrer was turned on and the magnetic speed was set to 350rpm to promote the mass transfer process of hydrophobic p-xylene. The composition of the anolyte: 50mmol / L phosphate buffer (composition: 10.36g / L Na2HPO4·12H2O, 3.32g / L NaH2PO4·2H2O, 0.31g / LNH4Cl and 0.13g / L KCl), 1mL / L trace element solution. The catholyte was a mixture of 250mL potassium ferrocyanide (50mmol / L) and potassium chloride (50mmol / L). The cathode and anode were connected through a 1 kΩ external resistor, and a Keithley multimeter was used to collect output voltage data, with one point collected every 10 min. The ambient temperature of the MFC reactor was 30 °C. The concentration of p-xylene was detected by a gas chromatograph (Agilent 7890B, USA), with the column box temperature set at 60 °C, the injection port temperature at 200 °C, and the detector temperature at 200 °C.
[0062] Comparative Example 3
[0063] On the basis of Example 2, two different MFC reactor systems, namely, the MR-1 system and the MR-1+Fe3O4@formed porous carbon ball system, were constructed.
[0064] MR-1 system: The electroactive bacteria Shewanella onesidensis MR-1 was selected as the inoculum, and the MR-1 suspension was dispersed in 250 mL of the anolyte until the OD 600The pH was 1.0, and then inoculated into the MFC reactor, and nitrogen was bubbled for 15 minutes to form an anaerobic environment. On the 0th day and the 2nd day, 10 μL of p-xylene liquid was added as the only carbon source and electron donor. Stirring was turned on to promote the mass transfer process of hydrophobic p-xylene. The magnetic stirrer was turned on and the magnetic speed was set to 350 rpm to promote the mass transfer process of hydrophobic p-xylene. The composition of the anolyte: 50 mmol / L phosphate buffer (formula: 10.36 g / L Na2HPO4·12H2O, 3.32 g / L NaH2PO4·2H2O, 0.31 g / L NH4Cl and 0.13 g / L KCl), 1 mL / L trace element solution. The catholyte was a mixture of 250 mL potassium ferrocyanide (50 mmol / L) and potassium chloride (50 mmol / L). The cathode and anode were connected through a 1 kΩ external resistor, and a Keithley multimeter was used to collect output voltage data, with one point collected every 10 min. The ambient temperature of the MFC reactor was 30 °C. The concentration of p-xylene was detected by a gas chromatograph (Agilent 7890B, USA), with the column box temperature set at 60 °C, the injection port temperature at 200 °C, and the detector temperature at 200 °C.
[0065] MR-1+Fe3O4@formed porous carbon ball system: Fe3O4@formed porous carbon balls synthesized in Example 1 were used, 5 g / L of Fe3O4@formed porous carbon balls were added to the anode chamber, and the electroactive bacteria Shewanella onesidensis MR-1 was selected as the inoculum. The MR-1 suspension was dispersed in 250 mL of the anode solution until the OD 600 The pH was 1.0, and then inoculated into the MFC reactor, and nitrogen was bubbled for 15 minutes to form an anaerobic environment. On the 0th day and the 2nd day, 10 μL of p-xylene liquid was added as the only carbon source and electron donor. Stirring was turned on to promote the mass transfer process of hydrophobic p-xylene. The magnetic stirrer was turned on and the magnetic speed was set to 350 rpm to promote the mass transfer process of hydrophobic p-xylene. The composition of the anolyte: 50 mmol / L phosphate buffer (formula: 10.36 g / L Na2HPO4·12H2O, 3.32 g / L NaH2PO4·2H2O, 0.31 g / L NH4Cl and 0.13 g / L KCl), 1 mL / L trace element solution. The catholyte was a mixture of 250 mL potassium ferrocyanide (50 mmol / L) and potassium chloride (50 mmol / L). The cathode and anode were connected through a 1 kΩ external resistor, and a Keithley multimeter was used to collect output voltage data, with one point collected every 10 min. The ambient temperature of the MFC reactor was 30 °C. The concentration of p-xylene was detected by a gas chromatograph (Agilent 7890B, USA), with the column box temperature set at 60 °C, the injection port temperature at 200 °C, and the detector temperature at 200 °C.
[0066] Test Example 3
[0067] The power generation performance of Example 2 and Comparative Example 3 was tested.
[0068] See also Figure 5-Figure 6 , the power generation of MFC reactors of three different systems, namely, the pure MR-1 system, the MR-1+Fe3O4@formed porous carbon ball system, and the MR-1+HN02+Fe3O4@formed porous carbon ball system, was compared. The initial voltages of the MR-1+Fe3O4@formed porous carbon ball system (128mV) and the MR-1+HN02+Fe3O4@formed porous carbon ball system (130mV) were both higher than that of the pure MR-1 system (47mV), which was attributed to the rapid electron transfer between the bacteria and the electrode interface caused by the presence of Fe3O4@formed porous carbon balls. In addition, the maximum output voltage of the pure MR-1 system was 154mV, the maximum output voltage of the MR-1+Fe3O4@formed porous carbon ball system was 165mV, and the maximum output voltage of the MR-1+HN02+Fe3O4@formed porous carbon ball system was 254mV, which was the highest power generation among the three systems. And by monitoring the concentration of p-xylene, it was found that the p-xylene removal rate of the system with the addition of Fe3O4@formed porous carbon balls was higher than that of the simple MR-1 system. On the one hand, it was because the porous structure of Fe3O4@formed porous carbon balls, as three-dimensional bioanode, was not only conducive to the adhesion, growth and reproduction of microorganisms, but also could enrich organic substrates and improve the bioanode conversion rate. On the other hand, Fe3O4@formed porous carbon balls, as magnetic electron mediators, could closely bind to the outer surface of bacteria, promote their extracellular electron transfer, accelerate the electron transfer between organic substrates and bacteria and between bacteria and electrode interfaces, and also act as a "bridge" between bacteria to enhance the interspecies electron transfer between Shewanella and Klebsiella, thereby improving the overall performance of MFC.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for enhancing electricity generation in microbial fuel cells by free magnetic carbon-rich three-dimensional bioanode and bacterial interface modification, characterized in that: The method for preparing the free magnetic carbon-rich three-dimensional bioanode comprises the following steps: (1) crushing biomass to obtain biomass powder, mixing the biomass powder with phenol and a catalyst to carry out a liquefaction reaction to obtain a biomass liquefied product; (2) reacting the biomass liquefaction product with formaldehyde to obtain a resin reaction product, and subjecting the resin reaction product to a hydrothermal reaction to obtain a hydrothermal reaction product; (3) mixing the hydrothermal reaction product and zinc chloride and placing the mixture in a mold, demolding, carbonizing, pickling, and washing with water to obtain a porous shaped carbon; (4) An iron source, trisodium citrate and ethylene glycol are mixed, added into the formed porous carbon and stirred, and then sodium acetate is added and mixed to obtain a mixed material, and the mixed material is subjected to a solvothermal reaction to obtain a free magnetic carbon-rich three-dimensional bioanode.
2. The method for enhancing electricity generation of microbial fuel cells by free magnetic carbon-rich three-dimensional bioanode and bacterial interface modification as claimed in claim 1, characterized in that: In step (1), the mass ratio of biomass powder to phenol is 1:1-6; the catalyst is one or more of sulfuric acid, phosphoric acid, and p-toluenesulfonic acid, and the mass ratio of the catalyst to biomass powder is 0.1-0.6:
1.
3. The method for enhancing electricity generation of microbial fuel cells by free magnetic carbon-rich three-dimensional bioanode and bacterial interface modification as claimed in claim 1, characterized in that: In step (1), the temperature of the liquefaction reaction is 120-170° C., and the reaction time is 0.5-5 h.
4. The method for enhancing electricity generation of microbial fuel cells by free magnetic carbon-rich three-dimensional bioanode and bacterial interface modification as claimed in claim 1, characterized in that: In step (2), the mass ratio of formaldehyde to biomass liquefaction product is 0.8-3:1, the temperature of the resinification reaction is 50-100°C, the resinification reaction time is 30-120min, the temperature of the hydrothermal reaction is 100-160°C, and the hydrothermal reaction time is 6-24h.
5. The method for enhancing electricity generation of microbial fuel cells by free magnetic carbon-rich three-dimensional bioanode and bacterial interface modification as claimed in claim 1, characterized in that: In step (3), the mass ratio of biomass powder to zinc chloride is 1:1.6-4.8, the shape of the mold is one of spherical, cylindrical, and cubic, the carbonization is carried out at 400-1000°C for 30-180min under a nitrogen atmosphere, the pickling is carried out using one of hydrochloric acid and sulfuric acid, and the concentration of the pickling is 0.1-2 mol / L.
6. The method for enhancing electricity generation of microbial fuel cells by free magnetic carbon-rich three-dimensional bioanode and bacterial interface modification as claimed in claim 1, characterized in that: In step (4), the iron source is one or both of ferric chloride and ferric nitrate, the iron source concentration is 0.05-0.35 mol / L, the trisodium citrate concentration is 8-80 mmol / L, the formed porous carbon concentration is 20-120 g / L, the sodium acetate concentration is 0.2-1.5 mol / L, the solvent thermal reaction temperature is 200-220°C, and the reaction time is 4-15 h.
7. The method for enhancing electricity generation of microbial fuel cells by free magnetic carbon-rich three-dimensional bioanode and bacterial interface modification as claimed in claim 1, characterized in that: The bacterium is the electroactive bacterium Shewanella onesidensis MR-1.
8. The method for enhancing electricity generation of microbial fuel cells by free magnetic carbon-rich three-dimensional bioanode and bacterial interface modification as claimed in claim 1, characterized in that: The OD of the Shewanella anolyte 600 It is 0.9-1.
1.
9. Application of a free magnetic carbon-rich three-dimensional bioanode and bacterial interface modification in the degradation of paraxylene.
10. The use according to claim 9, characterized in that The MFC reactor anode liquid also contains OD 600 It is 0.9-1.1 for Klebsiella HN02.
Citation Information
Patent Citations
Shewanella-decolorationis-based microbial fuel cell and using method thereof
CN102315471A
Preparation process of nano Fe3O4-V2O5-Au doped polythiophene membrane modified meshy glass carbon electrode
CN103151535A
Preparation method of extreme-micropore-enriched carbon material based on carboxylation anchoring effect
CN112340730A
Microbial fuel cell
US20110236725A1
